BIMBINGAN PRA-NIKAH TERHADAP KEHARMONISAN RUMAH TANGGA JEMAAT - samuel 17; Gregorius Suwito; Eni Rombe (JOURNAL of THEOLOGICAL STUDENTS, 2021)
The purpose of this study was to determine the influence of the prospective marriage's understanding of the pre-marital guidance material at the Beth-El Tabernacle Alfa Omega Gajah Mada-Semarang Church on congregational household harmony. The results of the first hypothesis proposed in this study are: Understanding of the Premarital Guidance Material in the 60% category is not accepted. The second hypothesis is that the harmony in the household of the congregation who has followed the Pre-Marriage Guidance is in the 60% category not accepted. The third hypothesis which is thought to have a positive influence between Pre-Marriage Guidance at the Beth-El Tabernacle Christ Church of Alfa Omega Semarang on household harmony is greatly accepted or has a positive relationship. Because the correlation coefficient value obtained is 723a, it is included in the high category in the correlation coefficient interpretation table.